2008
DOI: 10.1016/j.pec.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Where have all the copy letters gone? A review of current practice in professional–patient correspondence

Abstract: 2 ObjectiveThis article reviews the literature in relation to patients receiving copies of health professional correspondence. It examines progress in adopting the practice three years on from its introduction as policy in the UK, and considers potential benefits and obstacles to implementation. MethodsA review of the literature on copy correspondence, accessed via Medline, PubMed, CINAHL and also online resources, using the search terms "patient letter", "copy letter", "copy correspondence" and "doctor letter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 42 publications
0
56
0
Order By: Relevance
“…The provision of medical correspondence to patients has been suggested to improve shared decision making and promote the empowerment of patients . Consequently, the United Kingdom National Health Service (NHS) proposed a policy in 2000 outlining that ‘letters between clinicians about an individual patient's care will be copied to the patient as of right’ (NHS Plan, Paragraph 10.3) . This policy highlighted the need to provide patients with the option of receiving their medical correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…The provision of medical correspondence to patients has been suggested to improve shared decision making and promote the empowerment of patients . Consequently, the United Kingdom National Health Service (NHS) proposed a policy in 2000 outlining that ‘letters between clinicians about an individual patient's care will be copied to the patient as of right’ (NHS Plan, Paragraph 10.3) . This policy highlighted the need to provide patients with the option of receiving their medical correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…28 Prior studies have indicated that copying of correspondence to patients is associated with a range of benefits including greater patient understanding, greater patient involvement, reduction in anxiety, increased satisfaction, and more accurate risk perception. 29,30 Furthermore, a letter provides something that patients can share with relatives. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with observations made by Golodetz 12 more than 3 decades ago that "80 percent of patients felt they had understood enough to satisfy themselves." In a recent review, Baxter et al 33 noted that most of the reviewed studies demonstrated that patients accept medical terminology.…”
Section: Discussionmentioning
confidence: 99%